16 Adding capacity: getting EBP into the curriculum for all health professionals in ireland. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - O'Rourke, Niamh; Lehane, E; Agreli, H; O'Connor, S; Hegarty, J; Leahy-Warren, P; Bennet, D; Blake, C; Burke, F; Corrigan, M; Drennan, J; Hayes, M; et al.
Abstract : Objectives: Evidence Based Practice (EBP) is a cornerstone of delivering clinically effective care. An EBP capacity-building project commenced in Ireland in 2016, to build capability and leadership for EBP, with the ultimate goal of improving patient outcomes. A key part of this project was the development of a competency framework for education in evidence-based practice, to ensure responsiveness of education standards and curricula of healthcare professionals in this area. Develop a competency framework for healthcare professionals in EBP and clinical effectiveness education. Inform academic curricula and professional development programmes at third level. Provide a guide for attainment of knowledge, skills and attributes/behaviours for health service staff. Dissemination of the competency framework to Irish statutory health regulators and educators, to inform professional standards for registration courses and continuous professional development of healthcare professionals in Ireland. Method: Multiyear project (2016–2019): Baseline research on the teaching of evidence-based practice in Ireland; literature review, interviews with international experts and national survey of EBP teaching at third-level institutions Two national consultation events on EBP education in Ireland with regulators, researchers and educators Analysis of health regulators requirements in Ireland in relation to education and professional standards Development of a competency framework by UCC; documentary analysis of national and international documents pertaining to EBP and clinical effectiveness education; relevant competencies, curriculum considerations, teaching & learning methods and assessment strategies Stakeholder consultation; 13 focus groups with representatives from the health services, clinical practice, third level education & professional training sectors, regulator/accrediting bodies, and the Department of Health, to examine draft competency framework Policy makers in the Department of Health, health service providers and the regulators of health professionals (medicine, nursing and allied health professionals) convened an implementation group to oversee dissemination and implementation. Results: Evidence-based practice is a core component of clinical effectiveness. Additional competencies in quality improvement processes and implementation science strategies were deemed essential for patient outcomes. Professional practice competencies which addressed the need for effective communication, collaborative practice and leadership were specifically recommended. An overarching inter-disciplinary competency framework was proposed for clinical effectiveness education, which included the following domains: Evidence-based practice; Quality improvement processes; Implementation strategies and Professional practice. Stakeholders recommended the explicit integration of EBP competencies throughout academic and clinical learning domains of health professional curricula. Teaching methods recommended were based on an active learning approach and included: group-based projects; role-play/modelling; simulations and case-based studies that aid learners to apply and relate theory to real-world practice. Conclusions: A competency framework for clinical effectiveness education for health and social care professionals was published by the Department of Health in Ireland in 2018. It is intended that this framework will provide guidance to healthcare educators and regulators in the blueprinting of curricula, learning outcomes, assessment strategies, and graduate/clinician attributes. By means of consultation with stakeholders and working in collaboration with regulators and policy makers, we can translate evidence into policy and practice, to improve patient outcomes. Through inclusion of evidence-based practice in the curricula of all healthcare professionals at both undergraduate and post-graduate level, we aim to build capacity, educate health professionals to make informed choices, enhance real-world practice and encourage the next generation of leaders in evidence-based healthcare in Ireland.